2018
DOI: 10.7160/aol.2018.100301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Real Exchange Rate Volatility on Agricultural Products Export in Nigeria

Abstract: This study examines the effects of real exchange rate volatility on agricultural products export in Nigeria using annual time series data from1970 to 2013. The long run, short run and causal effects of real exchange rate volatility on agricultural products export were evaluated. VECM was used to evaluate the effects of real exchange rate volatility on agricultural products export. The Augmented Dickey-Fuller (ADF) and Philip Perron (PP) unit root tests confirm that all variables were stationary in their first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…Farmers do not know how to and do not have the means to export their products to the market. This problem is consistent with the extant literature (Alegwu et al, 2018; Azih, 2008; Elijah et al, 2017). Asenso-Okyere and Mekonnen (2018) noted that lessons from the Asian experience could help Africa, specifically that access to market information could help rural farmers become more competitive and productive.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Farmers do not know how to and do not have the means to export their products to the market. This problem is consistent with the extant literature (Alegwu et al, 2018; Azih, 2008; Elijah et al, 2017). Asenso-Okyere and Mekonnen (2018) noted that lessons from the Asian experience could help Africa, specifically that access to market information could help rural farmers become more competitive and productive.…”
Section: Discussionsupporting
confidence: 92%
“…Some rural Nigerian farmers do not have access to market data or know how to perform strategic planning. There was a lot of evidence to support this point in the literature, namely, Alegwu et al (2018), Dauda et al (2015), Kassali et al (2018), Magbadelo (2018) and Marketline (2017). The focus group participants felt Nigerian farmers do not treat farming as a business.…”
Section: Discussionmentioning
confidence: 94%
“…Using a general methods of moments model and panel data on 29 Chinese provinces for 1987-2008, Hua (2011) found that real exchange rate appreciation had a negative effect on both economic growth and employment. Alegwu et al (2017) examined the asymmetric effects of real exchange rate volatility on agricultural products export in Nigeria, using the VAR model and annual time series data for 1970-2013. Analysis using the real exchange rate volatility, measured as generalized autoregressive conditional heteroscedasticity (GARCH) (1, 1), showed that the effects of the real exchange rate volatility shock during appreciation and depreciation on most of the products were significantly different.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…GARCH (1,1) was used by [28] to measure real exchange rate volatility of Nigerian currency with a view to investigate the asymmetric effects of real exchange rate volatility on agricultural products export in Nigeria. Asymmetric effects test based on the Wald statistic showed that apart from cotton exports, the effect of currency volatility on cocoa, coffee and rubber exports was significantly different.…”
Section: Literature Reviewmentioning
confidence: 99%